2007
DOI: 10.1007/s12011-007-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Intranasally Instilled Fine Fe2O3 Particles into the Brain: Micro-distribution, Chemical States, and Histopathological Observation

Abstract: It has been demonstrated that inhaled fine (d < 2.5 microm) and ultrafine (d < 100 nm) particles produce more severe toxicity than coarse particles. Some recent data support the concept that the central nervous system (CNS) may be a target for the inhaled fine particulates. This work describes initial observation of the transport of intranasally instilled fine ferric oxide (Fe2O3) particles in animal brain. The iron micro-distribution and chemical state in the mice olfactory bulb and brain stem on day 14 after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 31 publications
2
90
0
Order By: Relevance
“…IONPs that will enter the brain via the blood-brain barrier (Wang et al, 2010;Yan et al, 2013) are likely to be covered by serum proteins and may slowly be taken up into neurons. In contrast, IONPs that may enter the brain via the olfactory pathway (Wang et al, 2007) or by direct injection into the brain for therapeutic reasons (Jordan et al, 2006;Maier-Hauff et al, 2011) are unlikely to be covered with serum proteins. Such particles may adsorb also in vivo very efficiently to neurons which could foster their internalization and metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IONPs that will enter the brain via the blood-brain barrier (Wang et al, 2010;Yan et al, 2013) are likely to be covered by serum proteins and may slowly be taken up into neurons. In contrast, IONPs that may enter the brain via the olfactory pathway (Wang et al, 2007) or by direct injection into the brain for therapeutic reasons (Jordan et al, 2006;Maier-Hauff et al, 2011) are unlikely to be covered with serum proteins. Such particles may adsorb also in vivo very efficiently to neurons which could foster their internalization and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…IONPs have been reported to enter the brain via the blood-brain barrier (Wang et al, 2010;Yan et al, 2013) and via the olfactory bulb (Wang et al, 2007) or are directly injected into the brain for therapeutic treatments (Jordan et al, 2006;Maier-Hauff et al, 2011). Thus, as brain cells will encounter IONPs, it is important to know about potential adverse effects of IONPs on these cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, NPs made of certain materials and with varying particle sizes can cross this physical carrier or enter the brain via the olfactory bulb nerve endings (Koziara et al 2006). In fact, Wang et al (2007) found that intranasal instillation of Wne Fe 2 O 3 particles (280 § 80 nm) caused neuronal fatty degeneration in the hippocampus, suggesting the possibility of an adverse impact of inhaled Wne Fe 2 O 3 particles on the CNS. The brain is particularly vulnerable to ROS damage, due to its high content of easily peroxidizable unsaturated fatty acids, high oxygen consumption rate, and relative paucity of antioxidant enzymes compared with other organs (Skaper et al 1999).…”
Section: Nervous Systemmentioning
confidence: 99%
“…In recent years, a large number of studies in animal models have demonstrated the ability of small molecular weight drugs, peptides and proteins to be transported directly from the nasal cavity to the central nervous system (CNS) [1][2][3][4][5][6][7][8] . However, the amount of drug transported via this route was shown to be small (well below 1%) and unless steps are taken by means of drug delivery technology to enhance the transport across the olfactory epithelium and/or via the olfactory and trigeminal nerves, this route is only therapeutically viable for very potent drugs 9 .…”
Section: Introductionmentioning
confidence: 99%